Comparison of Giving Extract of Piper betle with Different Concentration on Hatchability of Eggs and Survival of Nile tilapia Larva (Oreochromis niloticus) - Sholikha, Lailatuz Zakiatus; Lisminingsih, Ratna Djuniwati; Latuconsina, Husain (Agrikan Jurnal Agribisnis Perikanan, 2025)
The availability of tilapia (Oreochromis niloticus) is supported by the hatching speed which is influenced by internal and external factors as well as other factors such as disease. The microorganisms that usually attack fish eggs are fungi. Betel leaves are one of the plants that can be used for hatching eggs. The aim of this research was to compare the effect of different concentrations of betel leaf extract (Piper betle) on egg hatchability and survival of tilapia larvae (Oreochromis niloticus) and to determine the optimal concentration of betel leaf extract in supporting egg hatchability and survival of tilapia fish. larvae. This study used a Completely Randomized Design (CRD), P0: Control, P1: 0.08 mL/L, P2: 0.16 mL/L, P3: 0.24 mL/L, P4: 0, 32 mL/L L. Data analysis uses the ANOVA test and BNT test if there are significant differences. The results of the research showed that there was an effect of betel leaf extract on the hatchability of eggs and also on the survival of tilapia larvae (Oreochromis niloticus) in the P3 treatment concentration of 0.24 mL/L with success of 78.6% and 80%, respectively, the best results in the research. which is conducted. While egg hatchability and larval survival were lowest in the P4 treatment, namely at a concentration of 0.32 mL/L with success of 59.2% and 57%, this research showed less good results, where egg hatching was poor and the survival rate This treatment is also less than optimal because high concentrations are toxic to fish eggs.